Pengaruh Hafalan Al-Qur'an Juz 30 Terhadap Hasil Belajar Mata Pelajaran PAI Siswa - Sajdah, Meilisa; Dwistia , Halen; Rosalinda, Shinta (Ar-Rusyd: Jurnal Pendidikan Agama Islam, 2023)
This research is to determine the effect of memorizing the Qur'an Juz 30 on the learning outcomes of PAI Class VII subjects in SMP Negeri 2 Anak Ratu Aji Academic Year 2021/2022. This research is a quantitative type with the research population of students of SMP Negeri 2 Anak Ratu Aji with research subjects 29 students in class VII. Data collection techniques using observation, documentation and questionnaire. It is known that students with memorization of Al-Qur'an Juz 30 out of 29 respondents are known to have 5 students with low categories of 17.3 %, 10 students with moderate categories of 34.4 %, high categories of 14 students with a percentage of 48.3 %. For learning outcomes of PAI subjects in grade VII students from 29 respondents, 9 students were known to be 31 %, 8 students with moderate categories of 27.6 %, and as many as 12 students entered in a high category of 41.4 %. The results showed f? 0.4896, it can be concluded that there is a significant influence between the implementation of the memorization of the Qur'an Juz 30 on student learning outcomes in PAI subjects.